Is Gender Equity Possible in Indian Society? - Adhikari, Harasankar (Journal of Gender and Power, 2019)
Gender differences are social ideals that develop within the matrix of compulsory heterosexuality. Gender differences in Indian society are deeply rooted. The movement and action for women’s equity and justice are also miss-rooted. It pushes women into to more danger. Therefore, achievement of women’s equity and justice in Indian society is far away. This paper focuses this argument and shows that matrix of gender education and gender practices should be changed and it should not be free from sexual lens. Otherwise, gender equity is far away or never be achieved to make gender balance in our society.